Does facility type and location impact upon patient experiences in emergency departments? Secondary analysis of a state‐wide, cross‐sectional survey. (19th January 2020) - Bull, Claudia; Crilly, Julia; Chaboyer, Wendy; Spain, David; Mulhern, Brendan; Fitzgerald, Gerard; Scuffham, Paul; Byrnes, Joshua
Abstract: Objective: To identify the extent to which patient experiences in the ED differ depending on facility type (based on bed numbers, services available and annual separations), and location (level of remoteness). Methods: Data from a 2015 state‐wide (Queensland, Australia) public ED patient experience survey were linked to sociodemographic and presentation‐related characteristics data. Survey items were individually scored (from 0 to 100), and averaged across 13 pre‐determined patient experience topic areas. Descriptive statistics were used to report on patient sociodemographic and presentation‐related characteristics. One‐way analysis of variance tests were used to identify associations between patient‐reported experience scores, facility types and location. Results: A total of 10 553 patients over the age of 16 years completed the survey. All patients reported scores above 75 for 7 of the 13 patient experience topic areas (0 = lowest score, 100 = highest score). Patients from very remote and outer regional EDs reported the highest scores for the topic Environment and facilities, and remote facility patients reported the highest scores for the topic Leaving the ED – Delays . The same two topic areas were scored most highly by patients from smaller facilities in comparison to principal referral hospital EDs. Conclusions: Patients attending smaller and more rurally located EDs reported more positive experiences than those attending larger, metropolitan EDs on two of the 13 topic areas. However, these differences were marginal. Future research should aim to determine what constitutes clinically meaningful differences between groups when comparing patient‐reported experience scores, and understand the characteristics of small and rural EDs that may be associated with better patient experiences.